PH-Independent two-photon fluorescent lysotrackers for real-time monitoring autophagy. Issue 12 (6th March 2018) - Wang, Wenjuan; Ning, Peng; Wang, Qi; Zhang, Wan; Jiang, Jun; Feng, Yan; Meng, Xiangming
Abstract : pH-Independent two-photon fluorescent lysotrackers were achieved to real-time track lysosomes and visualize the membrane fusion period of autophagy. Abstract : Two carbazole-based two-photon fluorescent lysotrackers with different electron-donating groups (a methoxyl group forLyso-MCO and a dimethylamino group forLyso-NCO, respectively) have been developed from simple starting materials via an only 2-step procedure. Both of them exhibit pH-independent and specific lysosome location with a rapid staining rate, high photostability and deep issue penetration along with large two-photon absorption action cross-sections. By virtue of the better two-photon absorption properties ofLyso-NCO, it was chosen to visually monitor lysosomal tracking and autophagy. Compared with the approach of GFP-LC3 for autophagy detection, lysotrackerLyso-NCO achieved efficient and real-time visualization of the membrane fusion period in the autophagy process through detecting the level of the co-localization coefficients betweenLyso-NCO and Mitotracker Red FM (MTR) in live cells.